1992
DOI: 10.1104/pp.100.2.902
|View full text |Cite
|
Sign up to set email alerts
|

Flavonols Stimulate Development, Germination, and Tube Growth of Tobacco Pollen

Abstract: The effect of anther-derived substances on pollen function was studied using pollen produced by in vitro culture of immature pollen of tobacco (Nicotiana tabacum L.) and petunia (Petunia hybrida). Addition of conditioned medium consisting of diffusates from in situ matured pollen strongly increased pollen germination frequency and pollen tube growth, as well as seed set after in situ pollination. Thin-layer chromatography and depletion of phenolic substances by Dowex treatment indicated that flavonols are pres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
94
0

Year Published

1995
1995
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 185 publications
(97 citation statements)
references
References 27 publications
2
94
0
Order By: Relevance
“…Flavonoids are present in pollen of many species of Angiosperm and Gymnosperm and in spores of moss and ferns [18] . Particularly kaempferol and quercetin are two required flavonols to pollen tube germination and growth in tobacco [18] , petunia and maize [19] .…”
Section: Hplc/dad Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…Flavonoids are present in pollen of many species of Angiosperm and Gymnosperm and in spores of moss and ferns [18] . Particularly kaempferol and quercetin are two required flavonols to pollen tube germination and growth in tobacco [18] , petunia and maize [19] .…”
Section: Hplc/dad Analysismentioning
confidence: 99%
“…Particularly kaempferol and quercetin are two required flavonols to pollen tube germination and growth in tobacco [18] , petunia and maize [19] . However, these two flavonols have not been shown to carry a similar function in Arabidopsis [20] .…”
Section: Hplc/dad Analysismentioning
confidence: 99%
“…It has been reported that the accumulation of the flavonols is observed in stigma, ovaries, pollen grains and pollen tubes [20][21][22] . Moreover, it has also been reported that flavonols stimulate development, germination, and pollen tube growth of tobacco [1]. Reduction of flavonols has been demonstrated to assign to abnormal microspore, pollen development and pollen tube growth [23][24][25] .…”
Section: Discussionmentioning
confidence: 99%
“…as a side branch of the phenylpropanoid pathway are a principal component of pollen pigments. It has been suggested that one role of these flavonoids is to function during pollen germination and pollen tube growth in many plant species [1,2]. It has also been suggested that the transition of phenylpropanoids to flavonoids is essential for the development of viable pollen grains [3,4].…”
Section: Introductionmentioning
confidence: 99%
“…Petite Havana SR1 plants were grown in a growth chamber at 25°C with a 16-h light/8-h dark regime. Transgenic tobacco plants containing dc3-hgB and 35S-uidA constructs were produced by leaf disk transformation using the disarmed Agrobacterium tumefaciens LBA4404 as described by Horsch et al (12 16]. In these modified conditions, high germination frequencies could be achieved.…”
Section: Methodsmentioning
confidence: 99%